2020
DOI: 10.1080/02670844.2020.1754623
|View full text |Cite
|
Sign up to set email alerts
|

Physical and electrical properties’ evaluation of SnS:Cu thin films

Abstract: This paper reports successful fabrication of copper-doped tin sulphide (SnS:Cu) thin films using nebulized spray pyrolysis. Different Cu doping concentrations (2, 4, 6, and 8 wt-%) were employed to coat SnS:Cu thin films. The fabricated SnS:Cu thin films were structurally confirmed by X-ray diffraction and Raman scattering analyses. Energy-dispersive X-ray result has proved Cu atom doping within the SnS matrix. Atomic force microscopy has identified topographical modifications on SnS:Cu thin films due to Cu do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…In addition, similar observations were reported previously, 45 where the E g increased from 1.34 to 1.43 eV after Ag doping in SnS thin films. The same trends 67 have been observed for Cu-doped SnS thin films by other researchers. 68 A reduction in E g and red shift was also observed by Sebastian et al 69 for Al doping in SnS thin films, where the value of E g reduced from 1.5 to 1.29 eV.…”
Section: Optical Analysissupporting
confidence: 90%
“…In addition, similar observations were reported previously, 45 where the E g increased from 1.34 to 1.43 eV after Ag doping in SnS thin films. The same trends 67 have been observed for Cu-doped SnS thin films by other researchers. 68 A reduction in E g and red shift was also observed by Sebastian et al 69 for Al doping in SnS thin films, where the value of E g reduced from 1.5 to 1.29 eV.…”
Section: Optical Analysissupporting
confidence: 90%
“…Some of studies on Cu doped SnS lms which exist in the literature reported that Cu doping led to shrinkage in band gap of SnS lms until the certain Cu doping concentration and enlarged for further doping concentrations, regardless of the their crystal system [8,22,26,27]. Sebastian et al and Bommireddy et al stated that decrease in bad gap due to the increase in crystallite/grain size [22,26]. In this work variation in band gap may be related with the variation in crystallite size.…”
Section: Optical Analysismentioning
confidence: 61%
“…Optical band gap values of deposited lms were noted as 1.83 eV, 1.90 eV and 1.84 eV for SnS, SnS:Cu (4%) and SnS:Cu (8%) lms, respectively. Some of studies on Cu doped SnS lms which exist in the literature reported that Cu doping led to shrinkage in band gap of SnS lms until the certain Cu doping concentration and enlarged for further doping concentrations, regardless of the their crystal system [8,22,26,27]. Sebastian et al and Bommireddy et al stated that decrease in bad gap due to the increase in crystallite/grain size [22,26].…”
Section: Optical Analysismentioning
confidence: 99%
“…More magnesium atoms were positioned at the substitutional sites by increasing the doping concentration up to 10 atom %, which led to a successful integration of magnesium dopant into the SnS lattice and an increase in the occupied states and band gap. Similar results with doping in SnS with Cu, Pb, and Ag have been reported elsewhere. …”
Section: Resultsmentioning
confidence: 99%